The Role of Tourism in Enhancing Türkiye Soft Power: Challenges, Opportunities and Strategic Developments - EL OUALI, SARAH (İstanbul Kültür Üniversitesi, 2025)
This work examined the effect of tourism on Türkiye's soft power. It looks at the historical, cultural, and ecological richness of Türkiye with an emphasis on how tourism contributes to impact the global image of the country. The research discusses about the tourism economic contributions, cross-cultural exchanges, and international marketing campaigns by organizations like the Türkiye Tourism Promotion and Development Agency (TGA). But also about issues and recommendations, including racism, regional inequalities, and the role of the Turkish diaspora. International collaborations, CSR, and medical tourism are also examined as important facets of Türkiye's soft power. This work evaluates Türkiye's challenges, opportunities, and role in using tourism to gain international influence by carefully analyzing these fields.
Keywords: Türkiye Foreign Policies; Tourism; Soft Power